Interpretations arising from Wrightian and Malthusian fitness under strong frequency dependent selection. Issue 5 (3rd April 2013) - Wu, Bin; Gokhale, Chaitanya S.; van, Matthijs; Wang, Long; Traulsen, Arne
Abstract Fitness is the central concept in evolutionary theory. It measures a phenotype's ability to survive and reproduce. There are different ways to represent this measure: Malthusian fitness and Wrightian fitness. One can go back and forth between the two, but when we characterize model properties or interpret data, it can be important to distinguish between them. Here, we discuss a recent experiment to show how the interpretation changes if an alternative definition is used.